Danos e a hospedabilidade de cultivares de arroz a Meloidogyne graminicola e a ocorrência de nematoides em regiões orizícolas no Rio Grande do Sul - Rodrigues Júnior, Gerson Luís dos Santos (2024)
The rice cultivation can experience productivity reductions due to at least 29 species of nematodes. Approximately 20% of the total estimated economic losses attributed to nematodes stem exclusively from rice crop. Among the nematode species reported in the state of Rio Grande do Sul, Meloidogyne graminicola has the highest capacity for damaging the crop. However, there is a gap of information regarding the distribution of plant parasitic nematodes (PPN) in rice plantations in this state, as well as the multiplication capacity and damages caused by M. graminicola in Brazilian rice cultivars. Faced with this gap of knowledge, the present study aimed to conduct nematode survey in irrigated rice cultivation and to investigate the extent of the impact of M. graminicola on development, productivity, and nematode multiplication in Brazilian rice cultivars. To achieve this, root and soil samples were collected from different rice-producing regions in the state. Extraction and quantification of present nematodes were performed. Wasilewska Index (WI), Plant Parasites Index (IPP), and Food Chain Complexity Index (CCA) were used to assess the functional structure of the nematode community, along with calculations of nematode abundance and the relative frequency of PPN and facultative PPN. To determine the damage caused by M. graminicola in the development of Brazilian cultivars, two experiments were conducted, one in a dryland system and another in a flood system. In both experiments, the cultivars GURI INTA CL and IRGA 424 RI were exposed to increasing levels of initial inoculum (0 (control), 125, 250, 375, 500, 625, 750, 875, e 1000 eggs per 250 cubic centimeters of substrate), and after 60 days, parameters of development and nematode multiplication were assessed. To verify host suitability, 24 accessions were assessed for the final population, number of nematodes per gram of root, and the reproduction factor (RF). The survey revealed that non-flooded periods allow the survival of nematodes of different trophic groups and of PPN of different genera in the areas. It was also observed that those of the genera Meloidogyne, Hirschimanniella and Apelenchoides are widely distributed across the rice-producing regions of the state of Rio Grande do Sul, with Meloidogyne spp. being the most frequent in the samples. The analysis of damage revealed that in both cultivation systems, the reduction in aboveground growth was more pronounced from 500 eggs per 250 cc, and higher populations were found at levels of 375 and 500 eggs per 250 cc under flood and dryland conditions, respectively. Finally, it is noteworthy that the cultivar IRGA 421 exhibited the lowest RF after 60 days.